No Countries for Old Technology Assessment? Sketching the Efforts and Opportunities to Establish Parliamentary TA in Spain and Portugal - Knud Böhle; António Moniz (Technikfolgenabschätzung – Theorie und Praxis, 2015)
If the question is whether there is a parliamentary technology assessment (PTA) unit in Portugal or Spain, the clear answer is that there is still no such unit at the central state level at the present time, neither in Portugal nor in Spain. The question then has to be modified addressing previous and current efforts to establish PTA and the current framework conditions and opportunities. Practices of PTA are framed here as a democratic innovation in the context of changes in representative democracies. Against this backdrop, the efforts and opportunities to establish PTA in Spain and Portugal are studied. By sketching these developments and outlining the opportunities in these countries, our aim is to contribute to the debate about the likelihood of a new wave of PTA in Europe (Hennen/Nierling 2014).
Keywords: P11; H11; 330; technology assessment; parliament; Portugal; Spain